Efektivitas Intervensi Community Health Worker dalam Pelayanan Kesehatan: A Systematic Review - Jimni Maulana; Ferry Efendi; Setho Hadisuyatmana (Universitas Pahlawan Tuanku Tambusai, 2026)
The risk of heart disease and stroke can be reduced with adequate cardiovascular disease prevention, as outlined in the American Heart Association's Life's Essential 8 guidelines for modifiable health behaviors. This review examines the role of Community Health Workers (CHWs) in CVD prevention trials across the United States. In the 24 clinical trials identified, our review emphasized the effectiveness of CHWs in improving health behaviors and outcomes, particularly for underserved populations with limited access to health care. CHWs were actively involved in implementing interventions, providing culturally sensitive education, offering health coaching, and supporting lifestyle modifications, such as increased physical activity and medication adherence. It is noteworthy that most studies focused on heart disease. Beyond the CHW's role in delivering behavioral interventions, training for community health workers (CHWs) generally includes disease-specific knowledge and communication skills. CHW training programs vary widely in scope and standards, with unclear role definitions and inadequate collaboration. To improve CHW-led preventive health care, it is recommended to develop a standardized training framework, define CHW responsibilities in clinical and research collaborations, and build sustainable community-academic partnerships. This action could significantly enhance the role of CHWs in reducing cardiovascular disease (CVD) disparities, thereby promoting more equitable health care.